Mycoplasma synoviae elongation factor thermo stable is an adhesion-associated protein that enters cells by endocytosis and stimulates DF-1 cell proliferation - Yunhai Zhao; Haiyun Ma; Qing Wang; Xiaoxiao He; Xiaoyong Xing; Xiaochun Wu; Guomei Quan; Shijun Bao (BMC Veterinary Research)
Abstract Mycoplasma synoviae is an important avian pathogen that causes respiratory infections and arthritis symptoms in chickens and turkeys, resulting in significant economic damage to the poultry farming industry worldwide. Cell adhesion is a vital stage of Mycoplasma infection, and the proteins associated with this process play an important role in its pathogenesis. Elongation factor thermo stable (EF-Ts) is an important factor in prokaryotic biosynthesis that serves as a guanosine exchange factor for elongation factor thermo unstable (EF-Tu). To date, little is known about the role of EF-Ts in Mycoplasma infection. In this study, we identified EF-Ts as an immunogenic protein in M. synoviae through liquid chromatography with tandem mass spectrometry (LC–MS/MS) screening. We constructed an E. coli recombinant expression vector and prepared a highly efficient rabbit antiserum. Immunoblot analysis and suspension immunofluorescence revealed that the EF-Ts is located in both the cell membrane and cytoplasm. The prepared rabbit EF-Ts antiserum exhibited complement-dependent Mycoplasma-killing activity and inhibited the adhesion of rEF-Ts and M. synoviae to DF-1 cells. An in-vitro binding assay showed that EF-Ts could bind to fibronectin (Fn) and chicken plasminogen (cPlg) in a dose-dependent manner. In addition, EF-Ts could internalize into cells through lipid rafts and clathrin-dependent endocytosis and induce DF-1 cell proliferation. In conclusion, our studies demonstrated that MS EF-Ts is a potentially immunogenic, novel adhesion protein that acts as a critical virulence factor in M. synoviae adhesion to host cells during infection. These studies further deepen our understanding of the pathogenic mechanism of M. synoviae.